PENGARUH RELIGIUSITAS TERHADAP KECEMASAN AKADEMIK MAHASISWA - Siti Khoirun Nisa, M. Fahli Zatrahadi; Miftahuddin (STAI Nurul Falah Airmolek, 2026)
ABSTRAK Academic anxiety is a psychological problem frequently experienced by students due to academic demands, such as assignments, exams, competition for achievement, and pressure to complete studies. This condition can impact students' concentration, motivation, academic achievement, and even mental health. One factor believed to be able to help students cope with academic pressure is religiosity. This study aims to analyze the influence of religiosity on students' academic anxiety and examine the role of Islamic counseling in helping overcome academic anxiety. The research method used is library research by reviewing various national journals, books, and scientific articles over the past five years. Data were collected through documentation techniques and analyzed using content analysis methods. The results of the study indicate that religiosity has a negative relationship with academic anxiety, where the higher the level of religiosity of students, the lower their level of academic anxiety. Religious practices such as prayer, dhikr, supplication, reading the Quran, and an attitude of tawakkul (religious surrender) have been shown to provide inner peace, increase self-control, and help students cope with academic pressure more positively. Furthermore, Islamic counseling approaches such as dhikr therapy, devout prayer therapy, and Islamic spiritual strengthening are also effective in helping students reduce academic anxiety. Thus, religiosity and Islamic counseling can be alternative approaches to supporting student mental health in higher education settings.